Hsp90 inhibitors are efficacious against Kaposi Sarcoma by enhancing the degradation of the essential viral gene LANA, of the viral co-receptor EphA2 as well as other client proteins. - Wuguo Chen (Public Library of Science (PLoS), 2012)
Heat-shock protein 90 (Hsp90) inhibitors exhibit activity against human cancers. We evaluated a series of new, oral bioavailable, chemically diverse Hsp90 inhibitors (PU-H71, AUY922, BIIB021, NVP-BEP800) against Kaposi sarcoma (KS). All Hsp90 inhibitors exhibited nanomolar EC(50) in culture and AUY922 reduced tumor burden in a xenograft model of KS. KS is associated with KS-associated herpesvirus (KSHV). We identified the viral latency associated nuclear antigen (LANA) as a novel client protein of Hsp90 and demonstrate that the Hsp90 inhibitors diminish the level of LANA through proteasomal degradation. These Hsp90 inhibitors also downregulated EphA2 and ephrin-B2 protein levels. LANA is essential for viral maintenance and EphA2 has recently been shown to facilitate KSHV infection; which in turn feeds latent persistence. Further, both molecules are required for KS tumor formation and both were downregulated in response to Hsp90 inhibitors. This provides a rationale for clinical testing of Hsp90 inhibitors in KSHV-associated cancers and in the eradication of latent KSHV reservoirs.